Usahawan Pelajar UiTM Negeri Sembilan - mula muda / Dr Asiah Ali, Dr Raja Mayang Delima Mohd Beta and Nabilah Abdul Shukur - Ali, Asiah; Mohd Beta, Raja Mayang Delima; Abdul Shukur, Nabilah (UiTM Cawangan Negeri Sembilan, 2022)
Profile - Shopee that focuses on guiding people about the strategy and technique to start selling at Shopee. Education - UiTM Cawangan Neceri Sembilan Kampus Seaemban, Diploma in Public Administration & Policy Studies - January 2018 - September 2020. Bachelor at Corporate Administration - Currently studying. Recipient of the DEAN Award 2 semesters in Diploma in Public Administration. Deputy President of Intellectual students Affairs 2018-2019 President of the Gerakan Pengguna. Siswa 2019-2020. Treasurer of the Gerakan Pengguna Siswa 2021-2022. Spiritual Exco of the DiPAC Association Secretariat. Program Director for Program Trip to Election Commission for students from Diploma in Public Administration. Bulb Form Program Director: How to Volunteer? in collaboration with NGO MOVE. Active NGO volunteers in Kuala Lumpur 2020,2021. Received invitations as Instructors and Panel Members for the Consumerism Forum.